Анализ многовыходных схем гидропневмоавтоматики - Черкашенко, Михаил Владимирович (НТУ "ХПИ", 2005)
The method of the analysis based on construction of the simplified table of various statuses only for inputs of control of valves is offered. On the basis of the analysis possible schemes of realization of functions with use of valves are given.
Keywords: распределительная аппаратура; таблицы состояния; управляющие входы